Reason Al-Narajil as Gender-Just Jurisprudence: Analysis of the Roles of Women and Men - Rohmi Yuhani'ah; Yuslina Mohamed; Rudi Santoso (Brajamusti Publication, 2025)
This article is about the concept of Al-Narajil reasoning as an interpretation approach based on gender-just fiqh. The facts in society nevertheless point to the inequality between men and women, which has an impact on the subordination of their roles in public and domestic. So there needs to be a reinterpretation in the gender approach in order to achieve a partnership between the two. This article aims to analyze how Al-Narajil reasoning can provide a moreover inclusive and fair reinterpretation of gender issues, especially in the relationship between men and women, and their roles in society. The method used is qualitative, which emphasizes the analysis of religious texts and literature studies with a critical hermeneutic approach to Al-Narajil reasoning with comparative theory, library research type. The results of the study show that Al-Narajil reasoning offers space for reinterpretation of texts that are often considered gender biased, by emphasizing the principles of justice (al-'adl) and welfare (al-maslahah). This approach can be a foundation for building a moreover equal understanding of gender in the context of contemporary Islam, while responding to the challenges of modernity without ignoring the spiritual and ethical values of Islam. Al-Narajil rational idea offers a new perspective on the renewal of Islamic law, especially in the context of justice between men and women.